مغل برصغیر میں مذہبی رواداری اور علمی و سماجی ترقی : غیر مسلم مورخین کی آرا کا مطالعہReligious Tolerance and Scientific and Social Development in the Mughal Subcontinent: A Study of Non-Muslim Historians (Al-Qamar, 2021)
The present study investigates the perspectives of Non-Muslim historians regarding religious tolerance and scientific and social development in the Mughal Subcontinent. It traces the relationship between Mughals' tolerant attitude and the development of the subcontinent. It finds that Mughals gave rise to a culture in which the color of tolerance was prominent. Unlike the British, Mughals did not try to impose their language and culture on the Indians by force, but by tolerance they won their hearts and left a significant impact on the subcontinent. Non–Muslim historians have proved that the interfaith harmony of the Mughals played an important role in the development of the subcontinent. Findings of this study can be a rich source of guidance and inspiration to create interfaith harmony in the present day societies.
Keywords: Subcontinent; Mughals; tolerance; development